VD_FINDINFO Jug-inc / 2011 / 7 vom 3. Februar 2011 - VD Tribunal cantonal (2011)
ATTRACTION DE COMPÉTENCE, PROROGATION DE FOR, CONTRAT D'AGENCE, CONTRAT DE TRAVAIL, COMPÉTENCE | 147 CPC, 17 CPC, 58 al. 1 CPC, 58 al. 2 CPC, 59 al. 1 CPC, 61 al. 1 CPC, 91 CPC, 92 al. 1 CPC, 147 CPP, 21 LFors, 24 LFors, 5 LFors, 9 al. 1 LFors, 2 al. 1 TAv, 404 CPC (CH), 406 CPC (CH)